Identification and molecular characterisation of malaria parasites of macaques in Kapit, Sarawak - Divis, Paul Cliff Simon (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The objectives of this study were to develop species specific polymerase chain reaction (PCR) primers for molecular detection of monkey malaria parasites and to use molecular methods to identify and characterize plasmodium species from macaques. Since P. knowlesi is potentially of zoonotic origin, these methods would assist in determining whether macaques are the natural reservoir of P. knowlesi in the Kapit Division. In this study, species-specific PCR primers for the identification of P. knowlesi, P. cynomolgi, P. coatneyi, P. fieldi, P. inui and P. fragile were developed based on the variable regions in the small subunit ribosomal RNA (SSU rRNA) genes.